1979
DOI: 10.2307/145322
|View full text |Cite
|
Sign up to set email alerts
|

Econometric Studies of Labor-Labor Substitution and Their Implications for Policy

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. University of Wisconsin Press andThe Board of Regents of the University of Wisconsin System are collaborating with JSTOR to digitize, preserve and extend access to The Journal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
76
2
7

Year Published

1983
1983
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(94 citation statements)
references
References 19 publications
9
76
2
7
Order By: Relevance
“…22 The results are available upon request. 23 Hamermesh and Grant (1979) and Maskus and Bohara (1985), among others, discuss why specifications based on cost functions may be preferred to those motivated by profit functions. Also, see Christensen and Greene (1976) and Morrison (1992).…”
Section: Robustness Checksmentioning
confidence: 99%
“…22 The results are available upon request. 23 Hamermesh and Grant (1979) and Maskus and Bohara (1985), among others, discuss why specifications based on cost functions may be preferred to those motivated by profit functions. Also, see Christensen and Greene (1976) and Morrison (1992).…”
Section: Robustness Checksmentioning
confidence: 99%
“…There does not seem to be consensus as to an approximate value for the labour-labour substitution elasticity, and this is reflected by the fact that there is a rather large range of variation in the elasticity estimates, from 0.14 to 7.5 (Hamermesh and Grant 1979). 8 The big differences in the elasticity estimates can be the result of major methodological differences, such as the choice of estimating a cost or a production function, the choice of functional forms, the choice of data (time-series versus cross-section), and the disaggregation of the labour force according to various criteria, among others.…”
mentioning
confidence: 99%
“…Letting i represent blue-collar labor, j white-collar labor, and k capital, they found with manufacturing data going back to 1929 that the degree of substitution of i and j for k is very far from being the same. Instead, white-collar labor is complementary with capital in the previous study, or at least far less substitutable for capital than blue-collar labor (Daniel Hamermesh and James Grant 1979). By contrast, Carmel Chiswick (1985) has found that the long-run elasticity of substitution of physical capital for each of the two levels of human capital is much higher (about 2.5) than between capital and a single labor aggregate (less than unity).…”
Section: Cross-sectional Aggregatesmentioning
confidence: 71%